Ghrelin receptor deletion reduces binge‐like alcohol drinking in rats. (16th January 2019) - Zallar, Lia J.; Beurmann, Silvia; Tunstall, Brendan J.; Fraser, Claire M.; Koob, George F.; Vendruscolo, Leandro F.; Leggio, Lorenzo
Abstract : Ghrelin is a gastric hormone that has been implicated in the neurobiology of alcohol drinking. We have recently developed a ghrelin receptor (growth hormone secretagogue receptor; GHSR) knockout (KO) rat model, which exhibits reduced food consumption and body weight. In addition, recent preliminary work suggests that the gut‐microbiome, which appears to interact with the ghrelin system, may modulate alcohol drinking. In the present study, we investigated the effects of GHSR deletion on alcohol consumption utilising GHSR KO and wild‐type (WT) rats in three separate alcohol consumption paradigms: (i) operant self‐administration (30‐minute sessions); (ii) drinking in the dark (DID) (4‐hour sessions); and (iii) intermittent access (24‐hour sessions). These paradigms model varying degrees of alcohol consumption. Furthermore, we aimed to investigate the gut‐microbiome composition of GHSR KO and WT rats before and after alcohol exposure. We found that the GHSR KO rats self‐administered significantly less alcohol compared to WT rats in the operant paradigm, and consumed less alcohol than WT in the initial stages of the DID paradigm. No genotype differences were found in the intermittent access test. In addition, we found a significant decrease in gut‐microbial diversity after alcohol exposure in both genotypes. Thus, the present results indicate that the ghrelin system may be involved in drinking patterns that result in presumably increased alcohol exposure levels. Furthermore, GHSR may constitute a potential pharmacological target for the reduction of binge‐alcohol consumption. The potential functional role of the gut‐microbiome in alcohol drinking, as well as interaction with the ghrelin system, is an interesting topic for further investigation.